Concept for a LNG Gas Handling System for a Dual Fuel Engine - Michael Rachow; Steffen Loest; Leonardo Risman Maruli Sitinjak (International Journal of Marine Engineering Innovation and Research, 2017)
Nowadays, ships are using LNG as main engine fuel because based on the facts that LNG has no sulphur content, and its combustion process, LNG produces low NOx content compared to heavy fuel oil and marine diesel oil. LNG is not only produces low gas emission, but may have economic advantages. In the engine laboratory of maritime studies department in Warnemunde, Germany, there is a diesel engine type MAN 6L23/30 A, where the mode operation of these engine would be changed to dual fuel engine mode operation. Therefore, in this thesis, the use dual fuel engine will be compared where it will utilize natural gas and marine diesel oil and select the required components for fuel gas supply system. By conducting the process calculation, engine MAN 6L23/30 A requires the capacity natural gas of 12.908  for 5 days at full load. A concept for LNG supply system would be arranged from storage tank until engine manifold. Germanischer Lloyd and Project Guide of dual fuel engine will be used as a guidelines to develop an optimal design and arrangement which comply with the regulation.